Designers' guide to EN 1992-1-1 and EN 1992-1-2. Eurocode 2 design of concrete structures general rules and rules for buildings and structural fire design - Beeby, A. W. (Eurocode designers' guide series., 2005)
Eurocode 2 will apply to the design of building and civil engineering structures in plain, reinforced and pre-stressed concrete.